Regulation of CD44 expression and focal adhesion by Golgi phosphatidylinositol 4‐phosphate in breast cancer. Issue 7 (24th June 2016) - Ijuin, Takeshi; Takeuchi, Yukiko; Shimono, Yohei; Fukumoto, Miki; Tokuda, Emi; Takenawa, Tadaomi
Abstract : CD44, a transmembrane receptor, is expressed in the standard or variant form and plays a critical role in tumor progression and metastasis. This protein regulates cell adhesion and migration in breast cancer cells. We previously reported that phosphatidylinositol‐4‐phosphate (PI(4)P) at the Golgi regulates cell migration and invasion in breast cancer cell lines. In this study, we showed that an increase in PI(4)P levels at the Golgi by knockdown of PI(4)P phosphatase SAC1 increased the expression of standard CD44, variant CD44, and ezrin/radixin phosphorylation and enhanced the formation of focal adhesions mediated by CD44 and ezrin/radixin in MCF7 and SK‐BR‐3 cells. In contrast, knockdown of PI 4‐kinase IIIβ in highly invasive MDA‐MB‐231 cells decreased these factors. These results suggest that SAC1 expression and PI(4)P at the Golgi are important in tumor progression and metastasis and are potential prognostic markers of breast cancers. Abstract : Phosphatidylinositol‐4‐phosphate (PI(4)P) at the golgi regulated CD44 expression and focal adhesion formation in breast cancer cells. Knockdown of PI(4)P phosphatase SAC1 increased expression of CD44s and CD44v in breast cancer cells. Taken together, our results provide evidences that Golgi PI(4)P regulates breast cancer cell invasion and motility.